No overt influence of lymphadenectomy on cancer-specific survival in organ-confined versus locally advanced upper urinary tract urothelial carcinoma undergoing radical nephroureterectomy: a retrospective international, multi-institutional study - Burger, Maximilian; Shariat, Shahrokh F.; Fritsche, Hans-Martin; Martinez-Salamanca, Juan Ignacio; Matsumoto, Kazumasa; Chromecki, Thomas F.; Ficarra, Vincenzo; Kassouf, Wassim; Seitz, Christian; Pycha, Armin; Tritschler, Stefan; Walton, Thomas J.; et al. (World journal of urology, 2011)
Purpose Lymph node dissection (LND) is not routinely performed during radical nephroureterectomy (RNU) in upper tract urothelial carcinomas (UTUC), and its clinical relevance is unclear. The purpose of the present study was to evaluate the impact of LND on clinical outcomes in a large multicenter series of RNU for UTUC. Methods Detailed data on 785 patients subject to RNU were provided by nine international academic centers. The choice to perform lymphadenectomy was determined by the treating surgeon. All pathology slides were evaluated by dedicated genitourinary pathologists. Univariable and multivariable Cox regression models evaluated the association of nodal status with recurrence-free (RFS) and cancer-specific (CSS) survival. Results One hundred and ninety patients had LND. Pathological N stage was pN0 in 17%, pNx in 76%, and pN+ in 7%. The median follow-up period of the entire cohort was 34 months (interquartile range [IQR]: 15–65 months). Overall, five-year RFS and CSS estimates were 72.2 and 76%, respectively. In multivariable Cox regression analyses, pN0/pNx substaging was not an independent predictor of either RFS (hazard ratio [HR]: 1.1; P = 0.631) or CSS (HR: 1.3; P = 0.223). Similar results were obtained in a subgroup analysis limited to patients with organ-confined disease (HR: 0.9; P = 0.907 for RFS; HR: 0.4; P = 0.419 for CSS). Conversely, in patients with locally advanced disease, patients with pN0 disease have significantly better cancer-related outcomes (HR: 0.3; P < 0.001 for RFS; HR: 0.3; P < 0.001 for CSS). Conclusion The present series suggests pNx is more significantly associated with a worse prognosis than pN0, but only in patients with locally advanced UTUC.